Dynamic simulation for the rollover stability performances of articulated vehicles. (June 2014) - Yao, Zongwei; Wang, Guoqiang; Li, Xuefei; Qu, Junna; Zhang, Yuxin; Yang, Yonghai
This paper describes a dynamic model with four degrees of freedom for simulating the rollover stability performances of articulated loaders. The dynamic model considers three translational degrees of freedom and a rotational degree of freedom about the tilting axis and was verified by field experiments and virtual prototype experiments. The field experiments using a scaled articulated loader are detailed, and the experimental data of the lateral load transfer ratio, the lateral acceleration and the roll angle of the vehicle are provided for classification at different speeds and different turning radii. The virtual prototype experiments are modelled on the experimental model as well as the simulation conditions. Comparing the experimental data with the theoretical data shows that the dynamics model is reasonable and that the virtual prototype simulation can be used instead of the field experiments to improve the security of active safety technology development.